UK government delays restriction of promotions on less‐healthy foods: Serious implications for tackling obesity. Issue 9 (27th July 2022) - Moore, Sally; Butler, Tom
Abstract: Regulations ensuring that the promotion and advertising of foods high in fat, sugar, and salt were restricted from October 2022 are now to be delayed by the UK Government. The delay of this policy is to be condemned because it will set back the anticipated improvement to population diets and obesity levels by postponing the expected transformation of retail food environments in‐store and online. Governmental justifications for delaying these policies, the implementation of which was the responsibility of the UK food industry, can be perceived to reflect a short‐sighted willingness to use the current economic circumstances to push the responsibility for obesity and dietary choices back into the court of the consumer. Delaying these polices will, yet again, leave public health and clinical practitioners tackling obesity with less‐effective approaches focused on individual willpower and information provision.